The Tien Shan vole (Microtus ilaeus; Rodentia: Cricetidae) as a new species in the Late Pleistocene of Europe. Issue 22 (4th November 2021) - Baca, Mateusz; Popović, Danijela; Lemanik, Anna; Fewlass, Helen; Talamo, Sahra; Zima, Jan; Ridush, Bogdan; Popov, Vasil; Nadachowski, Adam
Abstract: Grey voles (subgenus Microtus ) represent a complex of at least seven closely related and partly cryptic species. The range of these species extends from the Atlantic to the Altai Mountains, but most of them occur east of the Black Sea. Using ancient DNA analyses of the Late Pleistocene specimens, we identified a new mtDNA lineage of grey voles in Europe. Phylogenetic analysis of mitochondrial DNA cytochrome b sequences from 23 voles from three caves, namely, Emine–Bair–Khosar (Crimea, Ukraine), Cave 16 (Bulgaria), and Bacho Kiro (Bulgaria), showed that 14 specimens form a previously unrecognized lineage, sister to the Tien Shan vole. The average sequence divergence of this lineage and the extant Tien Shan vole was 4.8%, which is similar to the divergence of grey vole forms, which are considered distinct species or being on the verge of speciation; M . arvalis and M . obscurus or M . mystacinus and M . rossiaemeridionalis . We estimated the time to the most recent common ancestor of the grey voles to be 0.66 Ma, which is over twice the recent estimates, while the divergence of the extant Tien Shan vole and the new lineage to be 0.29 Ma. Our discovery suggests that grey voles may have been more diversified in the past and that their ranges may have differed substantially from current ones. It also underlines the utility of ancient DNA to decipher the evolutionary history of voles. Abstract : We sequenced mtDNA from multiple Late Pleistocene vole specimens from three caves near the Black Sea. We discovered a new divergent lineage of grey voles (subg. Microtus ).